1941
DOI: 10.1104/pp.16.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Increase and Activity of Tobacco-Mosaic Virus Under Nitrogen-Deficient Conditions

Abstract: IntroductionAlthough viruses eause many plant diseases, little is known regarding their metabolism since they apparently multiply only in living tissue. Here it is difficult to differentiate between the metabolism of a host and that of a pathogen. Multiplication of viruses in vito is a well recognized fact and thermal inactivation in vivo of a few viruses has been definitely established. No other method for the inactivation of virus in vivo has been demonstrated experimentally.In this study on virus metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1941
1941
1956
1956

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Rishkov & Smirnova (1939) report that virus formation in tomato plants is unaffected by nitrogen starvation. This is contradicted by Spencer (1941), whose nitrogen-deficient tomato seedlings had constant contents of virus and total protein over a period when both increased fivefold in controls with adequate nitrogen. He found that virus protein was not utilized in severe nitrogen deficiency.…”
Section: Miscellaneous Effects Of Nitrogen Supply On Plantsmentioning
confidence: 94%
“…Rishkov & Smirnova (1939) report that virus formation in tomato plants is unaffected by nitrogen starvation. This is contradicted by Spencer (1941), whose nitrogen-deficient tomato seedlings had constant contents of virus and total protein over a period when both increased fivefold in controls with adequate nitrogen. He found that virus protein was not utilized in severe nitrogen deficiency.…”
Section: Miscellaneous Effects Of Nitrogen Supply On Plantsmentioning
confidence: 94%
“…A solution containing 51 rag. of disodium phosphate and 0.25 miUicuries of radioactivity was added to 4 pots containing medium-sized mosaic-diseased Turkish tobacco plants which had been grown in sand and fed with a complete nutrient solution as described by Spencer (1). After 48 hours, the plants were removed, their roots well washed, and the entire plants frozen.…”
Section: Methodsmentioning
confidence: 99%
“…Then each of 3 normal and 3 diseased plants from this group was fed 50 ml. of a nutrient solution prepared by adding 330 mg. of disodium phosphate containing 7 millicuries of radioactivity to 20 liters of the complete nutrient solution described by Spencer (1). The remaining diseased and normal plants were fed a nutrient solution prepared by adding 330 mg. of ordinary disodium phosphate to 20 liters of the complete nutrient solution.…”
Section: Methodsmentioning
confidence: 99%
“…In a former paper the writer (10) reported experiments which showed that the virus activity of juice expressed from tobacco plants diseased with tobacco mosaic was correlated with the amount of nitrogen supplied to the plants. No conclusions could be drawn from these experiments as to whether this increased activity was due to an increase in the rate of virus multiplication or to some other factor, such as greater accumulation of virus particles over a longer period of time, less destruction of virus, or greater dispersion of aggregates of virus particles.…”
Section: Introductionmentioning
confidence: 99%
“…of nutrient solution every other day and was supplied with water whenever necessary between nutrient applications. Low, medium, and high levels of nitrogen were maintained by the use of nutrient solutions, the composition of which has been described previously (10). As in the earlier work, the solutions were all supplemented with boron and manganese, as HI3BO3 and MnSO4 2H2O, respectively, at a concentration equivalent to 0.5 p.p.…”
Section: Introductionmentioning
confidence: 99%